Landscapes of the Itza : archaeology and art history at Chichen Itza and neighboring sites - Wren, Linnea Holmer; Kristan-Graham, Cynthia; Nygard, Travis; Spencer, Kaylee R., 1975- (University Press of Florida, 2018)
It has been fifteen years since a book was devoted to the new theories, paradigms, and investigations of archaeology and art history at Chichen Itza. The volume features five thematic foci: civic space, mythology through art, burials, trade, and landscapes. Due to the widespread awareness of this site, these themes appeal across the regional silos to reach all scholars of ancient America.